Association of Hypothyroidism and Subclinical Hypothyroidism with Covid-19 infection: A cross sectional study - Syed Anees Ahmed Gardezi, Syed Haider Tirmizi, Elleyyeen Avais, Muhammad Uzair, Muneeb ur Rehman, Hammad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A complex relationship of viral infections and the functionality of thyroid gland mainly due to a complex role of immunomodulatory signaling molecules, receptors and hormones. Aim: To check the Association of Hypothyroidism and Subclinical Hypothyroidism with Covid 19 infection. Study Design: Cross sectional study. Methodology: 100 patients presenting to emergency and medical OPDs or already admitted with Covid 19 infections were enrolled into the study. Only those admitted patients whose previous reports of thyroid profile were available and showed no anomaly, were included in the study. Presence of SARS-Cov-2 was confirmed using nasal or throat swab using reverse transcriptase polymerase chain reaction. 3ml blood sample was taken from the anticubital fossa of the patients under sterile conditions in Gel tube containing clot activator. Thyroid function tests of patients were carried out in automated analyzer by chemiluminescence method. Data was analyzed using SPSS version 25.0. Results: Out of total 100 patients 60 (60%) were male and 40 (40%) were females. Mean age of the patients was 40.6 ± 10.5 years. 54 (54%) of the patients had normal T3 levels where as 46 (46%) of the patients had below normal T3 levels. 47(47%) of the patients had lower T4 levels. TSH levels were normal in 50 (50%) patients whereas 35 (35%) had reduced levels and 15(15%) had raised levels. Mean T3 levels of study population was 2.04 ±1.1 pg/ml (0.1-4.1), T4 levels were 0.93 ±0.50 ng/dl (0.1-1.7) and TSH levels were 2.5 ±2.1 mIU/L (0.1-8.1). Prevalence of hypothyroidism was greater in our Covid population under study. 2 (2%) patients were diagnosed as having subclinical hypothyroidism. Conclusion: Presence and development of Hypothyroidism is significantly associated with SARs-Cov-2 viral infection. It has prognostic and diagnostic significant. Practical Implication: Due to the emerging nature of the COVID-19 crisis, this study helped researchers to investigate the functionality of thyroid gland due to Covid-19 infection. Keywords: Covid 19, endocrine disorder, hypothyroidism, Serum T3, T4, Thyroid gland, thyroid stimulating hormone.